Recycling of Methylthioadenosine is essential for normal vascular development and reproduction in Arabidopsis - Waduwara-Jayabahu, Ishari; Wirtz, Markus; Hell, Rüdiger (Plant physiology, 2012)
5′-Methylthioadenosine (MTA) is the common by-product of polyamine (PA), nicotianamine (NA), and ethylene biosynthesis in Arabidopsis (Arabidopsis thaliana). The methylthiol moiety of MTA is salvaged by 5′-methylthioadenosine nucleosidase (MTN) in a reaction producing methylthioribose (MTR) and adenine. The MTN double mutant, mtn1-1mtn2-1, retains approximately 14% of the MTN enzyme activity present in the wild type and displays a pleiotropic phenotype that includes altered vasculature and impaired fertility. These abnormal traits were associated with increased MTA levels, altered PA profiles, and reduced NA content. Exogenous feeding of PAs partially recovered fertility, whereas NA supplementation improved fertility and also reversed interveinal chlorosis. The analysis of PA synthase crystal structures containing bound MTA suggests that the corresponding enzyme activities are sensitive to available MTA. Mutant plants that expressed either MTN or human methylthioadenosine phosphorylase (which metabolizes MTA without producing MTR) appeared wild type, proving that the abnormal traits of the mutant are due to MTA accumulation rather than reduced MTR. Based on our results, we propose that the key targets affected by increased MTA content are thermospermine synthase activity and spermidine-dependent posttranslational modification of eukaryotic initiation factor 5A.